2018
DOI: 10.31234/osf.io/h3npq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Finding an emotional face in the kindergarten – Happiness superiority effect for children faces in pre-schoolers

Abstract: Previous studies investigating the advantage of emotional expressions in visual processing in preschool children only used adult faces. However, children perceive facial expression of emotions differently when displayed on adults’ compared to children’s faces. In the present study, pre-schoolers (N=43, Mean age=5.65) and adults (N=37, Mean age=21.8) had to find a target face displaying an emotional expression among eight neutral faces. Gender of the faces (boy and girl) were also manipulated. Happy faces were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Searching for studies with children we only found a few which met our criteria: 4 detection studies (see Supplementary Table 2A, Walden and Field, 1982; De Sonneville et al, 2002; LoBue, 2009; Zsido et al, 2018) and 2 identification studies (see Supplementary Table 2B, De Sonneville et al, 2002; Tottenham et al, 2013). In all but one of these studies, children's responses (from around 3 to 10 years of age) were compared to adults' responses, and indicated similar results across age.…”
Section: Review 2: Studies On Valence Effects In Face Processingmentioning
confidence: 99%
“…Searching for studies with children we only found a few which met our criteria: 4 detection studies (see Supplementary Table 2A, Walden and Field, 1982; De Sonneville et al, 2002; LoBue, 2009; Zsido et al, 2018) and 2 identification studies (see Supplementary Table 2B, De Sonneville et al, 2002; Tottenham et al, 2013). In all but one of these studies, children's responses (from around 3 to 10 years of age) were compared to adults' responses, and indicated similar results across age.…”
Section: Review 2: Studies On Valence Effects In Face Processingmentioning
confidence: 99%